Diversity of Human αβ T Cell Receptors - Kesmir, C.; Borghans, J.A.M.; Boer, R.J. de (My University, 2000)
(a = alpha) Arstila et al. (1) estimated an average diversity of 9 * 10^5 different b chains and 4.5 * 10^5 different a chains in the human nai¨ve T cell repertoire. To calculate the total T cell repertoire diversity, the b-chain diversity was estimated within a certain variable (V) gene family, Va12^+, comprising 2.5% of the total a-chain repertoire. Finding in this particular family an estimated total of 6 * 105 different ß chains (i.e., two-thirds of the total ß-chain repertoire), Arstila et al. suggested that the total T cell receptor (TCR) diversity comprises at least (6 * 105) * 40 = 2.4 * 10^7 different aß combinations (1). The authors acknowledge that this is only a lower bound, because the calculation assumes that the ß chains that do bind at least one Va12 chain bind only one of the 4.5 * 10^5 different a chains in the Va12^+ family. If each ß chain found within the Va12^+ family were to bind an average of n different Va12 chains instead, the total estimated TCR diversity would be n-fold higher than this lower bound.
Diversity of Human ab T Cell Receptors
Keywords: Biologie